The Diagnostic Value of Hba1c Turbidimetry Immunoassay in Sanglah General Hospital Denpasar, Bali, Indonesia - Anak Agung Wiradewi Lestari (Journal of Global Pharma Technology, 2018)
Introduction: Diabetes mellitus (DM) is a common health problem in Indonesia. Currently, Hemoglobin A1c (HbA1c) is the gold standard to diagnose and monitor DM patient. HbA1c could be assessed using turbidimetry immunoassay and High-Performance Liquid Chromatography (HPLC). However, the comparison between the two devices is never conducted. Thus, this study aimed to determine the sensitivity, specificity, and correlation of HbA1c measurements using turbidimetry immunoassay method compared to HPLC as the gold standard. Methods: A cross sectional study was conducted from May to June 2017to measure the diagnostic values and correlation test between turbidimetry immunoassay method and HPLC. Diagnostic values were measured as sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Blood samples were collected in EDTA tubes and measured with turbidimetry immunoassay and HPLC, with a cut-off value of 6.5 mg/dL. Results: Fifty samples were collected during the study. HbA1c ≥6.5mg/dL were obtained from 27 samples, and normal results were obtained from 23 samples. Sensitivity, specificity, PPV, and NPV from turbidimetry immunoassay were 92.86%, 100%, 100%, and 91.67% respectively. Pearson correlation test of HbA1c result from turbidimetry immunoassay and HPLC revealed a strong positive correlation with r = 0,988. The ROC curve analysis yield AUC value of 0.926 with P=0.000 which indicate a strong diagnostic value.Conclusion: Turbidimetry immunoassay method had high sensitivity and specificity and had strong diagnostic value according to ROC analysis. There was also a strong positive correlation between turbidimetry immunoassay and HPLC HbA1c reading.Keywords: HbA1c, HPLC, Turbidimetry immunoassay.